Appendix 5.5: Timeline from the Marcos Presidential Center Website - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
The Marcos Presidential Center website (www.marcospresidentialcenter.com) was perhaps the first attempt of the Marcos camp at having a stable pro-Marcos online presence. It is now defunct, apparently downed by hackers (Japanese characters appear onscreen when one visits the site nowadays). Besides the straightorward enumeration reproduced here, the website also features a year-by-year “clickable” carousel version of the following timeline. One major factual error that stands out is in the entry for 1970—the Plaza Miranda bombing happened in 1971. An appropriate entry would be the killing of protestors at Mendiola Bridge on 30 January 1970. The text under 1986 is a typical loyalist description of the EDSA Revolution; an ouster becomes a voluntary sacrifice by a heroic leader. Other features of the website as of 2 August 2002 were an online poll (“Should the government allow the Marcoses to inter FM’s body in the Libingan ng mga Bayani?”), an eight-entry bibliography consisting mostly of propaganda published during the Marcos regime, and a promise that the website will “have an online library of digital materials, such as video, audio, photographs, and printed materials documenting the life, work and family of the 6th President of the Republic of the Philippines.” That promise was never fulfilled; pro-Marcos social media pages/channels became online repositories for various “Marcosiana.”